Efficacy of Live Attenuated Dengue Vaccines: CYD-TDV, TDV (TAK-003), and TV003/TV005 - Hertanto, Yoseph Jeffry; Novita, Bernadette Dian (Folia Medica Indonesiana, 2021)
Highlight: • Differences in the efficacy of CYD-TDV versus the other TAK-003 and TV003/TV005 were discussed. • One licensed dengue vaccine is CYD-TDV (Dengvaxia). Abstract: Dengue fever is the most common tropical disease, but there still remains no specific therapy that can overcome it. Special attention needs to be paid to this disease, because there were large increases in incidence in the last decade. As an effective preventive strategy, finding a new vaccine for dengue fever with higher potentiation and efficacy is highly necessary to stop dengue transmission especially in the endemic area. Vaccine triggers an immune response, so that it can create a robust immune response when infected. Nowadays, there is only one licensed dengue vaccine that is CYD-TDV (Dengvaxia). However, this vaccine still has many weaknesses, namely its dependency on the serostatus of the recipient. There are also other dengue vaccines that are in ongoing clinical testing and have promising results, TDV (TAK-003) and TV003/TV005. These three vaccines are live attenuated vaccines with various results. This review discussed differences in the efficacy of CYD-TDV against the other TAK-003 and TV003/TV005; considering the known and unknown various factors.